Molecular Cloning, Genomic Organization, Developmental Regulation, and a Knock-out Mutant of a Novel Leu-rich Repeats-containing G Protein-coupled Receptor (DLGR-2) from Drosophila melanogaster - Eriksen, Kathrine Krageskov; Hauser, Frank; Schiøtt, Morten; Pedersen, Karen-Marie; Søndergaard, Leif; Grimmelikhuijzen, Cornelis J.P. (Genome Research, 2000)
After screening the Berkeley Drosophila Genome Project database with sequences from a recently characterized Leu-rich repeats-containing G protein-coupled receptor (LGR) fromDrosophila (DLGR-1), we identified a second gene for a different LGR (DLGR-2) and cloned its cDNA. DLGR-2 is 1360 amino acid residues long and shows a striking structural homology with members of the glycoprotein hormone [thyroid-stimulating hormone (TSH); follicle-stimulating hormone (FSH); luteinizing hormone/choriogonadotropin (LH/CG)] receptor family from mammals and with two additional, recently identified mammalian orphan LGRs (LGR-4 and LGR-5). This homology includes the seven transmembrane region (e.g., 49% amino acid identity with the human TSH receptor) and the very large extracellular amino terminus. This amino terminus contains 18 Leu-rich repeats—in contrast with the 3 mammalian glycoprotein hormone receptors and DLGR-1 that contain 9 Leu-rich repeats, but resembling the mammalian LGR-4 and LGR-5 that each have 17 Leu-rich repeats in their amino termini. The DLGR-2 gene is >18.6 kb pairs long and contains 15 exons and 14 introns. Four intron positions coincide with the intron positions of the three mammalian glycoprotein hormone receptors and have the same intron phasing, showing that DLGR-2 is evolutionarily related to these mammalian receptors. The DLGR-2 gene is located at position 34E-F on the left arm of the second chromosome and is expressed in embryos and pupae but not in larvae and adult flies. Homozygous knock-out mutants, where the DLGR-2 gene is interrupted by a P element insertion, die around the time of hatching. This finding, together with the expression data, strongly suggests that DLGR-2 is exclusively involved in development.[The nucleotide sequence(s) reported in this paper has been submitted to the GenBank/EMBL database with accession no. AF142343.]
10.1101/gr.10.7.924